Diving into Lake Devo: Modes of Representation and Means of Interaction and Reflection in Online Role-Play - Koechli, Linda; Glynn, Maureen (International Review of Research in Open and Distributed Learning, 2014)
This paper outlines an action research project involving the development of an educational online role-playing website, known as Lake Devo. Designed in keeping with constructivist principles, the website is used in select post-secondary courses at Ryerson University and allows learners to work synchronously, using visual, audio, and text elements to create avatars and interact in online role-play scenarios. The website also provides an integrated area for debrief following role-play activities. The features of the website were deliberately intended to provide a viable alternative to text-only online role-play activities, while not requiring the highly sophisticated elements of 3D virtual environments. During the period of the project on which this article reports, learners were invited to use the Lake Devo website for an assigned role-play activity. Online learner survey responses were collected following the pilot implementations of the website to determine the extent to which the non-text modes of representation (visual, audio) in Lake Devo, along with an integrated debrief area on the site, supported the learners in their online role-play activity. The preliminary findings suggest that Lake Devo provides an environment that effectively supports online role-play. The simple format of the Lake Devo avatars, the availability of visual and audio elements, and the ability to create a lasting artifact for review in a dedicated debrief area engage students and also reinforce the constructivist and collaborative nature of role-play activities. For practitioners beyond the Lake Devo project team and the Ryerson context, the Lake Devo website provides an example of an online role-play environment that offers alternatives to text-based and/or 3D virtual worlds.